2017
DOI: 10.11648/j.jher.20170303.12
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Quality of Groundwater in Keta South, Ghana

Abstract: Abstract:The paper investigated physico-chemical quality of groundwater, considering the relative proximity of hand dug wells to coastal environment, but most importantly close to insanitary facilities like refuse dumps, septic tanks and pit latrines; this was done in selected coastal communities in the Keta. Thirty vials of water samples from selected hand dug wells in two seasons were tested for pH, Total Dissolved Solids (TDS), Conductivity, Turbidity, Calcium, Magnesium, Nitrate, Sulphate, and Phosphate; W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…We attribute the brackish nature of water to the influence of the sea through seawater intrusion and/or deposition of atmospheric sea aerosol, dissolution of minerals and infiltrating wastewater in the neighborhood of the wells. Similar to our findings for Accra and Winneba, another study [ 23 ] reported higher values of EC/TDS in the wet season compared to the dry season in their work in the Keta area. It is difficult to explain the observed higher EC/salinity values in the rainy season compared to the dry season for Accra and Winneba; it is common for the vice versa to be observed and usually attributed to dilution in concentrations of chemicals and other physical water quality parameters during the wet season and evaporation in the dry season increasing concentrations of chemical parameters and physical quality values.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We attribute the brackish nature of water to the influence of the sea through seawater intrusion and/or deposition of atmospheric sea aerosol, dissolution of minerals and infiltrating wastewater in the neighborhood of the wells. Similar to our findings for Accra and Winneba, another study [ 23 ] reported higher values of EC/TDS in the wet season compared to the dry season in their work in the Keta area. It is difficult to explain the observed higher EC/salinity values in the rainy season compared to the dry season for Accra and Winneba; it is common for the vice versa to be observed and usually attributed to dilution in concentrations of chemicals and other physical water quality parameters during the wet season and evaporation in the dry season increasing concentrations of chemical parameters and physical quality values.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the Keta area is made up of unconsolidated sediments with a high possibility of entrainment of these loosely held sediments into flowing water during the wet season. A study in the Keta area made similar findings [ 23 ]. The high turbidity recorded in wells in Accra during the dry season cannot be explained, we speculate the possible seepage of wastewater into the shallow groundwater system of the area.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations